Pelatihan Penggunaan Aplikasi Mendeley bagi Mahasiswa Semester Akhir Program Studi PPKN, Fakultas Keguruan dan Ilmu Pendidikan Universitas Pattimura - Louisa M. Metekohy; Titus Gaite; Agustinus Nindatu; Jurgen Litualy (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Training on Using the Mendeley Application for Semester Students of the PPKN Study Program, Faculty of Teacher Training and Education, Pattimura University, is an activity aimed at enabling students to use the Mendeley Application when completing their final writing. This training is also to increase students' understanding of the dangers of plagiarism as part of academic misconduct. . Through lecture methods, discussions and interactive activities, students are encouraged to understand the use of the Mendeley application when writing research proposals, research results and theses. The results of this program show active participation from students as well as increased student understanding of using the Mendeley application and in the future students will be able to use it in writing, thus this activity also reduces plagiarism crimes.